Getting started with Oracle BPM Suite 11gR1 : a hands-on tutorial : learn from the experts--teach yourself Oracle BPM Suite 11g with an accelerated and hands-on learning path brought to you by Oracle BPM Suite Product Management team members /: a hands-on tutorial : learn from the experts--teach yourself Oracle BPM Suite 11g with an accelerated and hands-on learning path brought to you by Oracle BPM Suite Product Management team members. (2010) - Unknown
No abstract available